"Comparative Analysis of Laparoscopic Fundoplication and Magnetic Sphincter Augmentation for the Treatment of Medically Refractory GERD". Issue 11 (November 2018) - Richards, William O.; Mcrae, Carly
We have recently introduced laparoscopic magnetic sphincter augmentation (MSA) combined with hiatal hernia repair for treatment of patients with medically refractory gastroesophageal reflux disease (GERD). MSA is a novel surgical approach to the treatment of severe GERD, in which magnetic beads are secured around the lower esophageal sphincter, augmenting the lower esophageal sphincter function as an anti-reflux barrier. We hypothesize that patients undergoing MSA will achieve GERD relief, equal to that obtained after laparoscopic Nissen fundoplication. The GERD Health Related Quality of Life (GERD HRQL) Questionnaire is a validated clinical tool that was used to quantify patient outcomes in terms of GERD-related symptoms both on and off proton pump inhibitors and after acute radiation syndrome. We retrospectively reviewed data from patients at our institution enrolled in a prospective institutional review board–approved database "Registry Outcomes Anti-Reflux Surgery" that applies objective and subjective information about patients undergoing anti-reflux surgery. Information from both the database and patient HRQL scores were used to compare the effectiveness of medical intervention with acute radiation syndrome (laparoscopic Nissen fundoplication and MSA) in decreasing GERD-related symptoms in patients. Results are expressed as mean ± SE, and single-factor ANOVA test was used to compare groups. We found that MSA and laparoscopic fundoplication both lead to a comparable decrease in HRQL score and an increase in patient satisfaction when compared with patient's preoperative symptoms with maximum proton pump inhibitor use. In addition, our study shows that MSA is a safe minimally invasive anti-reflux procedure without the negative side-effects, such as gas bloat, inability to belch, and inability to vomit, commonly associated with NF.